IMPACT ANALYSIS ON IMPLEMENTATION OF ONBOARD TRAINING MONITORING BASED ON MOBILE APPLICATION - Harris R Dahlan; Rizqiya Windy Saputra; Muhammad Aziz (Jurnal Maritim Malahayati, 2022)
The existence of a practical learning model is a requirement for prospective merchant marine students in an effort to develop their experience dealing directly with the world of work. Merchant Marine Polytechnic Malahayati requires cadets to carry out Onboard Training (Prala) in their educational syllabus. However, the role of educational institutions in monitoring the activities of cadets when practicing outside the campus is currently a bit neglected. This can be caused by several factors, including the absence of tools/or instruments that can monitor the activities of cadets directly. Previous research on the development of a mobile-based application prototype to monitor the performance of cadets in Prala activities became one of the instruments for improving the education sector. This follow-up research uses quantitative methods and R&D research method to approach the solution to the problems obtained based on the implementation objectives. The final goal of the research is the availability of an impact analysis from the information database on the application of digitizing prala activities through a mobile-based application prototype. The results of this analysis can be used by policy makers at the Malahayati Poytechnic of Merchant Marine in developing a better education monitoring system outside the collage in the future.